A study of influence on nanocomposite membrane of sulfonated TiO2 and sulfonated polystyrene-ethylene-butylene-polystyrene for microbial fuel cell application. (August 2015) - Ayyaru, Sivasankaran; Dharmalingam, Sangeetha
Abstract: Microbial fuel cell (MFC) is a device that uses bacteria as a catalyst to oxidize various substrates for simultaneous electricity generation and wastewater treatment. In the present work, (sulfonated TiO2 (S-TiO2 )/polystyrene ethylene butylene polystyrene) SPSEBS nanocomposite membranes were prepared by solution casting. The IEC (ion exchange capacity), water uptake, proton conductivity and MFC performance of the composite membranes were explored. SPSEBS-S-TiO2 membrane (7.5%) exhibited the highest IEC value, water uptake and proton conductivity capacity. The results revealed that the incorporation of sulfonated TiO2 improved the proton conductivity of the SPSEBS membrane effectively and exhibited the highest peak power density of 1345 ± 17 mWm −2 for SPSEBS-S-TiO2 7.5%, when compared to 695 ± 7 mWm −2 and 835 ± 8 mWm −2 obtained for SPSEBS and SPSEBS-TiO2 membranes respectively in a (single chambered microbial fuel cell) SCMFC. In comparison to previously reported work with Nafion (300 ± 10 mWm −2 ) in MFCs, the composite membrane delivered more than 4-fold higher power density. The oxygen mass transfer coefficient (KO ) of nanocomposite membranes decreased with incorporation of the sulfonated TiO2 which in turn increased the (columbic efficiency) CE. Highlights: Novel SPSEBS-TiO2 -SO3 H membrane was prepared by solution-casting method. Exhibited highest IEC value, proton conductivity and MFC performance. The improved performance was due to the sulfonation effect of TiO2 –SO3 H particles. K O of composite membranes was lower than SPSEBS. The sulfonated composite membrane delivered 124% higher power density than SPSEBS.